1993
DOI: 10.1007/bf00230218
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a gamma-glutamyl-transferase-related gene family on chromosome 22

Abstract: A gene family encompassing a minimum of four genes or pseudogenes for gamma-glutamyl transferase (GGT; EC 2.3.2.2) is present on chromosome 22q11. We have previously isolated a cDNA related to GGT but clearly not belonging to its gene family. The chromosomal location of this related gene, GGTLA1, has been determined by both isotopic and fluorescence in situ hybridization to metaphase cells and by Southern blot analysis of somatic cell hybrid DNAs. We show that GGTLA1 is part of a distinct gene family, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The 22q11 region contains a large number of highly repetitive as well as intermediate repetitive sequences (10,13,14). There also is evidence that several genes may be duplicated in the region (15,57). The regions in which we have mapped the evolutionary breakpoints of human chromosome 22q11 correspond to regions containing these repetitive sequences.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 22q11 region contains a large number of highly repetitive as well as intermediate repetitive sequences (10,13,14). There also is evidence that several genes may be duplicated in the region (15,57). The regions in which we have mapped the evolutionary breakpoints of human chromosome 22q11 correspond to regions containing these repetitive sequences.…”
Section: Discussionmentioning
confidence: 92%
“…Human chromosome 22q11 has a high gene density, but it also contains several duplicated regions and low-copy repeat families. It has been suggested that the instability of the 22q11 region may be related to the presence of these numerous repeats (14,15).…”
mentioning
confidence: 99%
“…Some of the genes have been well characterized . The four known genes in the LCR22s are USP18 (Schwer et al 2000), GGT (Rajpert-De Meyts et al 1988), GGTLA (Heisterkamp et al 1991;Morris et al 1993), and BCR (Heisterkamp et al 1985). USP18 maps to LCR22-2, GGT maps to LCR22-8, GGTLA maps to LCR22-7, and BCR maps to LCR22-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The functional GGT gene (Rajpert-De Meyts et al 1988) maps to LCR22-8, but unprocessed pseudogene copies (Morris et al 1993) map to other LCR22s and other loci in the genome (Fig. 1A,D).…”
Section: Duplication and Transposition Processes Of Ggtmentioning
confidence: 99%
“…However, Pawlak et al (1988) showed that at least four genes containing GGT sequences were present in the human genome. These are located at band q11 on chromosome 22 (Morris et al, 1993;Collins et al, 1997). Recently, It has been reported that the human GGT was encoded by a multigene family including at least seven genes.…”
Section: Yardimci 2000)mentioning
confidence: 99%